The Multistate Reliability Assessment of Ship Hull Girders - Joanna Soszyńska-Budny; Špiro Ivošević (Applied Sciences)
Ships are designed to withstand various types of hull structure damage, including corrosion, fatigue, damage, crack, fouling, etc., throughout their projected life cycle of 25 years. In this study, we used a database of 25 different bulk carriers aged from five to twenty-five years, consisting of a total of 1920 thickness measurements of girder plate damage across 110 fuel tanks. Thickness measurements of longitudinal girder plate were conducted by certified technicians and approved company. Ultrasound thickness gauging equipment was used to collect data in accordance with the developed methodology and gauging scheme. Based on the classification societies’ rules, the values of the reduction in steel plate thickness due to corrosion over time fall into three categories: acceptable corrosion, substantial corrosion, and extensive corrosion. While classification societies prescribe permissible thickness reductions between 15 and 30%, in this study, the authors considered the excessive corrosion values to be above 20% reduction in initial thickness. Measurements indicating more than 20% reduction were classified as failures, necessitating the replacement of the corroded surfaces. After applying the multistate approach to the reliability analysis of longitudinal girder plates and improving reliability after reaching the critical state, the results show that usability dropped significantly between ten and fifteen years of service for upper girder plating and between twenty and twenty-five years of service for lower girder plates. These findings highlight the crucial impact of gauging location on reliability analysis.